Analisis Tindak Tutur Direktif Pada Akun Tik Tok @Vmuliana dan Relevansinya Sebagai Penyusunan Handout - Gina Raehani; Oding Supriadi; Hendra Setiawan (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to describe the form and function of directive speech acts on the Tik Tok account @vmulian and their relevance as a preparation of material handouts for writing job application letters in class XII. This research is motivated by the Tik Tok application which is currently loved by social media users, both children and adults. In addition, this research is motivated by the problems faced in the digital era 4.0 that one of the requirements for applying for a job is to attach a curriculum vitae to a job application letter. However, students' knowledge and ability to write a job application letter accompanied by a curriculum vitae is still very low. Because in learning Indonesian at school, they don't deepen the learning. The method used in this research is descriptive qualitative method. The data collection technique in this study is the documentation technique in the form of video. The research subject is in the form of videos on the Tik Tok account @vmuliana, one of the Tik Tok accounts as one of the educational content. Then the results of the analysis of this study, found 48 data. The results of the speech act analysis were used as handout teaching materials for writing job application letters in class XII. The selection of the type of handout teaching materials aims to convey job application letter material more easily.